Analisis Pengaruh Mekanisme Internal Good Corporate Governance Terhadap Profitabilitas Perusahaan - Rekha Dwi Anggraeni; Benny Barnas; Radia Purbayati (Journal of Applied Islamic Economics and Finance, 2022)
This study aims to determine the effect of the Internal Good Corporate Governance Mechanism proxied by the Board of Directors, Board of Commissioners, Independent Commissioner, and Audit Committee on Profitability as measured by ROA and ROE. The data used is secondary data obtained from 14 Annual Reports of companies that are members of the infrastructure, utilities, and transportation sectors registered at ISSI for the period 2016–2020.The research method used is quantitative research with panel data regression analysis. The results of this study indicate that the Board of Directors, Board of Commissioners, Independent Commissioner, and the Audit Committee simultaneously have no effect on ROA and ROE. Meanwhile, the partial test results show that on the dependent variable of ROA, only the Independent Commissioner has a positive and significant influence on ROA. Meanwhile, for the dependent variable ROE, there is no independent variable that has an effect on ROE.